Parathyroid adenoma in a 15-year-old girl with recurrent urolithiasis - Kucaba, Patrycja; Dziadzio-Gąsior, Katarzyna; Podlasek, Robert; Bar, Piotr; Korczowski, Bartosz (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The incidence of urolithiasis in children has been growing steadily for several decades, and it accounts for an increasing percentage of hospitalizations. Kidney stones are deposits of various mineral salts. Most of them are composed of calcium, favored by hypercalcemia and hypercalciuria. Primary hyperparathyroidism is one of the reasons for increased calcium levels in the blood. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. A 15-year-old girl was hospitalized due to recurrent urolithiasis. Investigations revealed hypercalcemia with elevated parathyroid hormone. Ultrasound of the thyroid gland showed a local change near the lower pole of its right lobe, and Sestamibi nuclear scan confirmed the presence of the adenoma of the lower right parathyroid gland. Surgical removal of the parathyroid gland with the present adenoma was performed. Calcium and phosphate homeostasis parameters and the kidneys’ ultrasound image were without any significant deviations from the norm. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. After finding the cause of recurrent urolithiasis, the applied surgical treatment resolved all disease manifestations.